2015
DOI: 10.1016/j.celrep.2015.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Cdc42EP3/BORG2 and Septin Network Enables Mechano-transduction and the Emergence of Cancer-Associated Fibroblasts

Abstract: SummaryCancer-associated fibroblasts (CAFs) are non-cancerous cells found in solid tumors that remodel the tumor matrix and promote cancer invasion and angiogenesis. Here, we demonstrate that Cdc42EP3/BORG2 is required for the matrix remodeling, invasion, angiogenesis, and tumor-growth-promoting abilities of CAFs. Cdc42EP3 functions by coordinating the actin and septin networks. Furthermore, depletion of SEPT2 has similar effects to those of loss of Cdc42EP3, indicating a role for the septin network in the tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
170
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(187 citation statements)
references
References 41 publications
13
170
2
2
Order By: Relevance
“…S6C). Consistent with the reported dependence of Factin assembly on Cdc42EP3 levels (Calvo et al 2015), the ability of MRTF 123-1A to induce activity of the YAP-TEAD reporter and YAP-TEAD target genes in NFs was sensitive to Cdc42EP3 depletion (Fig. 7H).…”
Section: Mrtf-srf Signaling Activates Yap Through Cell Contractilitysupporting
confidence: 73%
See 2 more Smart Citations
“…S6C). Consistent with the reported dependence of Factin assembly on Cdc42EP3 levels (Calvo et al 2015), the ability of MRTF 123-1A to induce activity of the YAP-TEAD reporter and YAP-TEAD target genes in NFs was sensitive to Cdc42EP3 depletion (Fig. 7H).…”
Section: Mrtf-srf Signaling Activates Yap Through Cell Contractilitysupporting
confidence: 73%
“…8H). YAP activation in CAFs is dependent on cell adhesion and contracility (Calvo et al 2013(Calvo et al , 2015. In normal fibroblasts, MRTF-SRF signaling potentiates YAP-TEAD signaling in an adhesion-and contractilitydependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a recent study showed that in vivo septins are required for the remodeling of the extracellular matrix by cancer-associated fibroblasts (CAFs). In addition, septins partly promote CAF-induced tumor growth and pro-angiogenic activity (Calvo et al, 2015). This is the first evidence of septins playing a role in the organization and properties of the tumor microenvironment, which is important for the progression of cancer.…”
Section: Emerging Roles Of Septins In Cancermentioning
confidence: 99%
“…In the case of the septin knockout mice with embryonic lethal phenotypes, podocyte-specific knockout mouse models are necessary for defining the role of these specific septins in the maintenance of glomerular ultrafiltration in higher vertebrates. A recent study revealed that septin network is required for the process of mechanotransduction (Calvo et al, 2015). Mechanical stimuli, including stretch, affect podocyte biology in vitro and play a significant role in the development of glomerulosclerosis in vivo (Schordan et al, 2013).…”
Section: Discussionmentioning
confidence: 99%